Structural and Luminescent Properties of a Cr3+/sm3+ Doped Gdalo3 Orthorhombic Perovskite for Solid-State Lighting Applications - Elhamdi, I.; Souissi, H.; Kammoun, S.; Dhahri, E.; Pina, J.; Costa, B. F. O.; Brito, A. L. B.; FAUSTO, RUI; Lopez-Lago, E. (Royal Society of Chemistry, 2025)
The Cr3+ and Sm3+ doped GdAlO3 perovskite with formula Gd0.995Sm0.005Al0.995Cr0.005O3, was synthesized via a solid-state reaction method, and its structure, morphology, and photoluminescence properties were thoroughly investigated. The compound crystallizes in the orthorhombic Pbnm space group, with Cr3+ transition-metal ions substituting Al3+ in the octahedral symmetry site, and Sm3+ lanthanide (rare-earth) ions occupying the tetrahedral site. The material's morphology and chemical composition homogeneity were evaluated through Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray analysis. Photoluminescence excitation (PLE) and emission spectra (PL) were used to shed light on the electronic structure of the Cr3+ cations, through crystal field analysis in the Oh symmetry site. Theoretical studies enabled the precise assignment of the Cr3+ 3d-3d transitions. The intra-configurational 4f-4f transitions of Sm3+ resulted in a variety of excitation bands appearing in the high-wavelength range of the PLE spectrum. The photoluminescence studies supported the occurrence of energy transfer in the doped GdAlO3 perovskite between Gd3+, Sm3+ and Cr3+ ions. The obtained results suggest the high potential of the synthesized material for solid state lighting applications.